Corrosion protection mechanisms of carbon nanotube and zinc-rich epoxy primers on carbon steel in simulated concrete pore solutions in the presence of chloride ions. (August 2016) - Cubides, Y.; Castaneda, H.
Highlights: The presence of carbon nanotubes in zinc-rich epoxy primer with 60 wt% zinc content influence the predominant barrier protection mechanism. The carbon nanotube and zinc-rich epoxy primer with 70 wt% zinc content were able to provide a good balance between mass transfer (barrier) and charge transfer (cathodic protection) mechanisms. For carbon nanotube and zinc-rich epoxy primers with 80 wt% and 90 wt% zinc content the dominant mechanism is cathodic protection. A porous protective layer of zinc corrosion products was formed at the coating surface with the highest Zn concentrations (80 wt% and 90 wt%). Abstract: This study investigates the electrochemical characterization of carbon nanotube and zinc-rich epoxy primers (CNT-ZRPs) on carbon steel in simulated concrete pore (SCP) solutions in the presence of chloride ions. The mechanistic performance of CNT-ZRPs was characterized by adding different zinc content. The electrochemical results indicated a dominant barrier protection effect for the coating with 60 wt% Zn while there was a mixed corrosion protection mechanism for the coating with 70 wt% Zn and a dominant cathodic protection mechanism for coatings with higher zinc content (80 wt% and 90 wt% Zn). These barrier and cathodic protection control mechanisms were characterized quantitatively by electrochemical and high-resolution techniques.